World prehistory - Fagan, Brian M., author.
1 online resource
Keywords: "This is an introduction to human prehistory written for complete beginners with a global perspective, written in a jargon-free style that covers 3 million years of the remote past from human origins to the first pre-industrial civilizations, balancing theoretical discussion with descriptions and analysis of major sites and cultural developments. World Prehistory provides a unique and balanced narrative of what happened in the prehistoric past and why. The book is well worth acquiring, as it provides essential historical background to a wide variety of subjects from written history and environmental studies to climate change. Chronological tables, numerous illustrations, guides to further reading, and stand-alone boxes on some archaeological methods, key sites, and some people of the past amplify much of the basic narrative. This global prehistory is aimed at people with no background in archaeology, undergraduates at all levels, and participants in graduate seminars on a wide range of subjects. Numerous people with a general interest in archaeology and multidisciplinary history have acquired and enjoyed this book"--